Recent Developments of Theory of Latent Structure Analysis - Asano, Chooichiro; Eshima, Nobuoki (Journal of the Japan Statistical Society, Japanese Issue, 1993)
In this survey article, a general view of the methodology of latent structure analysis is presented and some directions of further development are introduced. In the first section, the background of the latent structure analyses is described with the aim of the present article. In the subsequent sections, 2, 3 and 4, latent trait models, latent class models and latent structural equation model are discussed.